HEC-HMS Model for Urban Flood Analysis in Belik River, Yogyakarta, Indonesia - Slamet Suprayogi; Rifai; Reviana Latifah (ASEAN Journal on Science and Technology for Development, 2021)
The rapid development of Yogyakarta has made city development increase. This construction continues to expand the reach of impervious surfaces. As a result, surface runoff and maximum discharge have increased, overflowing up to urban drainage. This study aimed to analyze the maximum discharge of the watershed based on design storms with 2, 5, 10, and 25-year return periods, used for flood control considerations. The urban flood was modelled using HEC-HMS. The results showed that the contribution of discharge flow in each segment is influenced by the dominance of land use, in which the segment dominated by dense settlements has a high contribution to the maximum discharge. The flow contribution is due to the high curve number value, which corresponds to the high surface runoff. The peak discharge of watersheds with return periods of 2, 5, 10, and 25 years are 8 m3/s, 20.1 m3/s, 29.9 m3/s, and 44.1 m3/s, respectively.